Jerusalem Future Outlook Insights in the Noble Quran (Journal of Namibian Studies : History Politics Culture, 2023)
The people of the Book’s failure to shoulder the responsibility of the divine message had significant consequences. They were deprived from the great honour of holding the trust, and it was transferred to Ishmael’s children, to be completed and sealed by Prophet Muhammad (PBUH). That was also accompanied by major shifts. On the one hand, the Qibla came back to Mecca. On the other hand, the association between the Grand Mosque of Mecca and Al-Aqsa Mosque of Jerusalem constitutes a pivotal indicator of a continuous conflict between the new trust holders, Muslims, and those who deviated from the straight path, people of the Book. A number of forms of the conflict were mentioned in the Noble Quran, in which the latter exceeded the limits and offended mosques and other places of worship. As a result, they necessarily deserved present and future destruction. Divine rules are always valid against those who prohibit people from entering Almighty Allah’s mosques, since disgrace, fear, insecurity and instability shall be omens of their termination.